Managing the execution of large scale MPI applications on computational grids - Nascimento, Ad. P.; Sena, Ad. C.; Silva, J. A. da; Vianna, D. Q. C.; Boeres, C.; Rebello, V. E. F. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2005: Anais do XVII International Symposium on Computer Architecture and High Performance Computing, 2005)
Computational grids aim to aggregate significant numbers of resources to provide sufficient, but low cost, computational power to an ever growing variety applications. Writing applications capable of executing efficiently in these grid environments is however extremely difficult for inexperienced users. The grid's geographically distributed resources are typically heterogeneous, non-dedicated, and are offered without any performance or availability guarantees. This work investigates an alternative approach (based on smarter system-aware applications) to solve the problem of developing and managing the execution of grid applications efficiently. Results show that these system-aware MPI applications are indeed faster than their conventional implementations and easily grid enabled.